2019
DOI: 10.1074/jbc.ra119.009492
|View full text |Cite
|
Sign up to set email alerts
|

De novo dNTP production is essential for normal postnatal murine heart development

Abstract: Edited by John M. Denu The building blocks of DNA, dNTPs, can be produced de novo or can be salvaged from deoxyribonucleosides. However, to what extent the absence of de novo dNTP production can be compensated for by the salvage pathway is unknown. Here, we eliminated de novo dNTP synthesis in the mouse heart and skeletal muscle by inactivating ribonucleotide reductase (RNR), a key enzyme for the de novo production of dNTPs, at embryonic day 13. All other tissues had normal de novo dNTP synthesis and theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…We speculate that the variation in dATP levels could be related to ischemia during sample collection and delayed quenching of enzymatic activity. Similar to two chromatographic quantifications ( 6 , 23 ), we found heart dGTP concentration to be several-fold higher than that of other three dNTPs. Mitochondrial dNTP pools are extremely asymmetric with dGTP concentration being more than 10-fold higher than the concentration of other dNTPs ( 16 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We speculate that the variation in dATP levels could be related to ischemia during sample collection and delayed quenching of enzymatic activity. Similar to two chromatographic quantifications ( 6 , 23 ), we found heart dGTP concentration to be several-fold higher than that of other three dNTPs. Mitochondrial dNTP pools are extremely asymmetric with dGTP concentration being more than 10-fold higher than the concentration of other dNTPs ( 16 ).…”
Section: Discussionsupporting
confidence: 84%
“…( 6 ) and Tran et al. ( 23 ). Despite deviation in the absolute values, this reference data and our data showed highly similar dNTP pool asymmetry patterns for the mouse heart (Table 3 ).…”
Section: Resultsmentioning
confidence: 96%
“…We speculate that the variation in dATP levels could be related to ischemia during sample collection and delayed quenching of enzymatic activity. Similar to two chromatographic quantifications (6,22), we found heart dGTP concentration to be 5 to 15-fold higher than that of other three dNTPs. Mitochondrial dNTP pools are extremely asymmetric with dGTP concentration being more than 10-fold higher than the concentration of other dNTPs (23).…”
Section: Discussionsupporting
confidence: 82%
“…Nucleotide biosynthesis has received scant attention in skeletal MuSCs, but a recent study by Tran et al (2019) reported on ribonucleotide reductase (RNR) knockout mouse. In this study the authors developed a mouse model with exon 9 of the M1 subunit of RNR flanked by two loxP sites ( Rrm1 fl/fl ) and bred it with a mouse expressing Cre recombinase under the control of muscle creatine kinase ( Mck cre ), with the resulting mouse expressing a truncated and inactive form of RNR in cardiac and skeletal muscle from embryonic day 13 (Tran et al, 2019). As RNR is a key enzyme for de novo nucleotide synthesis, its conditional ablation allowed the investigators to study the importance of this pathway in skeletal and cardiac muscle.…”
Section: Nucleotide Synthesis Through the Pentose Phosphate Pathwaymentioning
confidence: 99%
“…While not described in detail, the authors found that muscle fibers in the gastrocnemius muscles of knockout mice were less than half the size of those observed in wildtype mice. Additionally, the number of nuclei per fiber was reduced by more than half (Tran et al, 2019). It will be critical in future studies to determine whether a similar defect in dGTP (as observed in cardiac muscle) is observed in skeletal muscle of RNR knockout mice.…”
Section: Nucleotide Synthesis Through the Pentose Phosphate Pathwaymentioning
confidence: 99%